Diversity and Otherness Transcultural Insights into Norms, Practices, Negotiations - Gaupp, Lisa; Pelillo-Hestermeyer, Giulia (De Gruyter, 2021)
This book critically examines multiple ways in which cultural diversity is, and has been represented and handled. It questions the construction of differences in doing culture while emphasizing the fluidity of cultural entanglements. It is an invitation to re-think norms, practices and negotiations of diversity and otherness, to distinguish emancipatory from standardizing approaches and to "transculturalize" the study and the politics of culture.